ANALISIS CLUSTER TERHADAP INDIKATOR DATA SOSIAL DI PROVINSI NUSA TENGGARA TIMUR MENGGUNAKAN METODE SELF ORGANIZING MAP (SOM) - Nurul Imani; Achmad Isya Alfassa; Anne Mudya Yolanda (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2022)
The Human Development Index (HDI) is used to assess the quality of life in a given area. In general, the HDI of Nusa Tenggara Timur (NTT) Province increased by 0.88 percent per year from 2011 to 2020 and fell by 0.06 percent in 2019-2020. The characteristics of the current situation of HDI in all districts/cities in NTT were defined using 9 variables in this study. The goal of this study is to combine clustering analysis with a Self-Organizing Map (SOM). Based on the analysis, it was found that NTT has four clusters based on HDI, with clusters 1, 2, 3, and 4 having 16, 3, 2, and 1 member(s) respectively. The cluster findings are meant to be utilized as a guide by the government when developing public policy or making decisions, given the seriousness of the Covid-19 pandemic. These findings could be used to address social issues in NTT, as well as be supported by beneficial policies.